Connected and fearful? Exploring fear of online financial crime, Internet behaviour and their relationship - Brands, Jelle (European journal of criminology, 2021)
Although it is generally acknowledged that the development of the Internet created new criminal opportunities, the ways this is experienced by the general population has received limited attention. The current study seeks to explore the degrees to which people report fear of online crime, its correlates, and how online fear is related to protective and avoidance behaviour. We focus on online financial crimes. Results based on a large, representative, survey indicate an intermediate level of fear of online crime among the general Dutch population. Various sociodemographic characteristics and victimization experiences are shown to predict fear of online financial crime. We also find online fear to be a strong predictor of avoidance behaviour, given negative relationships with online purchasing and banking, thereby impeding individuals’ perceived online freedom and opportunities. Finally, the results found no indications that fear may stimulate protective behaviour of one’s computer.